The ethno-racial segmentation jobs: The impacts of the occupational stereotypes on hiring decisions. Issue 6 (2nd November 2018) - Ndobo, André; Faure, Alice; Boisselier, Jeanne; Giannaki, Stella
ABSTRACT: This paper considers both the division of the labor market and the occupational stereotyping as explanatory mechanisms of discrimination in hiring decisions. It hypothesized that recruiters would favor candidates applying for a position that is stereotypically identified with their ethnic category. We solicited 146 recruiters in order to evaluate the hireability of either a native-born or an immigrant candidate, either competent or not competent, for either a prestigious or a low-skill occupation, and to justify their decision in writing. As predicted, both the hireability ratings and the narrative comments produced by recruiters showed that native-born applicants were preferred for prestigious jobs while immigrants tended to be selected more often for low-skill positions.The discussion addresses various issues related to decision-making in recruitment settings.